Tissue culture of Pyrethrum (Tanacetum cinerariifolium) and associated microbial contamination - Ambrožič-Dolinšek, Jana (Acta biologica slovenica, 2010)
Microbial contamination was observed on several subcultures of Pyrethrum (Tanacetum cinerariifolium) (Trevir.) Schultz-bip. callus lines. The presence of microorganisms was detected by isolation of contaminants in pure culture from 7 out of 34 callus lines and direct amplification of eubacterial 16S rDNA in the pyrethrum callus and plants and isolated bacteria. Altogether 16 contaminants were further analyzed, observing their morphology on several media and restriction of amplified 16S rDNA. Analysis revealed presence and persistence of morphologically and genetically diverse bacteria in pyrethrum tissue culture. Due to cross reactivity of 16S rDNA primers with DNA of plant origin, no conclusions could be drawn on the origin of contaminants.
Keywords: bolhač; kalusna kultura; kontaminacija; mikroorganizmi; PCR; polymerase chain reaction; Tanacetum cinerariifolium; tkivne kulture